THU0185 THE FIRST REPORT OF SIGNIFICANTLY IMPROVEMENT OF NT-PROBNP LEVEL IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH TOFACITINIB DURING 12-MONTH FOLLOW-UP. (June 2019) - Novikova, Diana; Kirillova, Irina; Markelova, Eugenia; Udachkina, Helen; Gerasimova, Helen; Luchihina, Helen; Karateev, Dmitriy; Demidova, Natalia; Misiyuk, Anna; Cherkasova, Maria; Popkova, Tatiana
Abstract : Background: The amino-terminal fragment of the B-type natriuretic peptide prohormone (NT-proBNP) is a marker for functional cardiac impairment and is increased in heart disease with or without symptoms of congestive heart failure (CHF) 1 . Objectives: To prospectively investigate the effect of tofacitinib (TOFA) on the levels of NT-proBNP, as a predictor of CHF in patients (pt) with active rheumatoid arthritis (RA). Methods: Twenty six RA pt (median age 54 [40;62] years, 81% female, disease duration 44[24;63, 0] month (m), moderate to high activity (DAS28-5.1[4.6;6.1], SDAI–27(22;35)), positive for ACCP (73%)/RF (77%), who were non-responders to MTX at least 15 mg/week and/or other synthetic DMARDs and bDMARDs) free of clinical overt cardiovascular disease were treated with TOFA and followed for 12 m. TOFA therapy was started in all pt in dose 5 mg BID per os with dose escalation to 10 mg BID in 8 (31%) pt. TOFA used in combination with MTX in 24 (92%) pt, leflunomide in 1 (4%). Low-dose oral corticosteroids (<10 mg/day prednisone or equivalent) were received by 9 (35%) pt. Remission was achieved in 38, 5% pt (DAS28), 38, 5% (SDAI). Cardiovascular risk factors (CVRF) and the NT-proBNP levels were measured at baseline and after 12m. At baseline the most of pt had multiple CVRF and subclinical organ damage. Cardioprotective therapy received 16 (57%) pt (β-AB–7, ARA/ACE inhibitors–11, statins–11, dihydropyridine CCB-7). Twenty controls matched for CVRF were included for comparison of normal NT-proBNP levels with those of RA pt. Results: The NT-proBNP level was significantly higher in RA pt than in the control group (median 62.2(26.9-101.7) pg/mL vs 44.0 (34.0-54.3) pg/mL, p<0.05). At baseline NT-proBNP level was higher in female than in male (p=0, 019). Its concentration correlated with DAS28 (r=0, 41, p=0, 036). Three pt (11, 5%) had NT-proBNP level over 125 pg/mL. All RA pt with a NT-proBNP level over 125 pg/mL were asymptomatic and exhibited normal echocardiography. Median DAS28 and SDAI were significantly reduced following TOFA treatment (from 5.1 to 2.9, p < 0.001 and from 26.8 to 4.7, p < 0.001, respectively). During follow-up, no RA pt exhibited a cardiovascular event or CHF. NT-proBNP levels decreased by 63% over the 12-m of TOFA treatment (from 62.16 pg/mL to 14.8 pg/mL, p= 0.011). The incidence rate of arterial hypertention (58%vs65%), overweight (62%vs62%), abdominal obesity (58%vs62%), smokers (27%vs27%), menopausal status (52%vs52%), DM type 2 (7%vs7%), mSCORE≥5% (23%vs27%), subclinical carotid atherosclerosis (58%vs58%) did not change significantly. An increase in body mass index (BMI) was observed from 26.5[22.9;29.0] to 26.9[24.0;30.1], p<0.001 and in HDL level from 1.37[1.06;1.87] to 1.90[1.29;2.16], p<0.01. The percentage change in the NT-proBNP level significantly correlated with the percentage change in the BMI (r=0, 6, p=0, 007), DAS 28 (r = 0.41, p = 0.038) SDAI (r = 0.51, p = 0.009). Changes in NT-proBNP levels in RA pt with remission was greater than that observed in pt who didn't achieve remission (-87% vs -26%, p=0, 005). The percentage change in the NT-proBNP level was not correlated with the percentage change in other CVRF. Conclusion: TOFA decreased the NT-proBNP level in patients with RA without clinical overt cardiovascular disease and CHF. TOFA may have a cardioprotective effect in those with active RA. Reference: [1] Breunig M., Kleinert S., Lehmann S. et al. Simple screening tools predict death and cardiovascular events in patients with rheumatic disease. Scand J Rheumatol2018;47(2):102-109. doi: 10.1080/03009742.2017.1337924. Disclosure of Interests: Diana Novikova: None declared, Irina Kirillova: None declared, Eugenia Markelova: None declared, Helen Udachkina: None declared, Helen Gerasimova: None declared, Helen Luchihina Speakers bureau: Pfizer, Abbvie, Biocad, Dmitriy Karateev: None declared, Natalia Demidova: None declared, Anna Misiyuk: None declared, Maria Cherkasova: None declared, Tatiana Popkova: None declared